Experimental analysis the effect of end mill flutes on delamination in milling of synthetic FRP composite. Issue 1 (March 2021) - Ling, M C H; Haliah, N H; Tan, C L; Azmi, A
Abstract: Fibre reinforced polymer (FRP) composites often employed the milling process to achieve the final geometrical shapes and dimensional tolerances. However, the random variations material properties and abrasiveness of FRP composite make the milling process become a challenge. An experimental approach has been committed in this study to analysis the effect of tool geometry in end-milling on unidirectional FRP composites with its machinability indices. The experiment methodology was conducted by altering the cutting tool geometry (number of flutes) and types of reinforcement fibres. Overall, the milling experiments induced various damages on FRP composite such as fibre pull-out, delamination and epoxy matrix interfacial de-bonding are associated to the rapid deterioration of tool sharpness. Besides that, the performance of four flutes end mill tool is distinguished with better surface finish when machining across carbon fibre orientation under same spindle speed and feed rate. This is likely due to the tool engagement during cutting process and nature properties of carbon FRP composite.